Fatigue damage modeling of fibrous soft tissues. Issue 1 (October 2016) - Linka, Kevin; Itskov, Mikhail
Abstract: Ultimate tendon failure is often caused by fatigue loading. Recent interventions revealed a three‐phase progression of histological changes during cyclic loading of the tendon. It starts from localized kinked fiber deformations, continues with additional fiber delaminations and finally leads to fiber angulations and discontinuities [5, 6]. In the present contribution, we propose a physically motivated constitutive model able to describe fatigue evolution in tendon subject to cyclic loading. The damage of the collagen fibers is elucidated by a successive permanent opening of tropocollagen molecules [7], which represent the basic building blocks of collagen fibrils. The fibril strain increase is triggered by a time‐force depending rupture of glycosaminoglycan sidechains of adjacent collagen fibrils. The so obtained model is in line with recent experimental findings available in literature. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)